Performance evaluation of World Wide Web over wireless networks - Ahmad, Nazrul Muhaimin (2006)
In this work, a Multilevel Pre-fetching (MLP) algorithm is proposed in conjuction with the weak cache consistency mechanism to enhance the frequency of updating cached objects. It is an extension to client polling mechanism and responsible for validating the cached objects without waiting for the requests from the clients. It is executed whenever the cache-server channel is under utilized.